Manajemen Konten Digital Pada Akun Instagram The Investor (Analysis of the SoMe Model) - Rahman, Ahmada Auliya (Borobudur Communication Review, 2025)
Instagram is one of the social media platforms used for communication activities, such as publications, public relations, and promotions to target audience. The Investor is a platform for learning safe, calm, and growing stock investments that can be accessed anytime and anywhere, owned by PT Indonesia Investa Origa. Amid the prevalence of online crimes in the form of fraud or illegal investments, The Investor emerges as an investment education platform for the public. In conducting its business, The Investor utilizes social media to interact and carry out marketing communication functions with its target audience. The purpose of this research is to describe the management of The Investor's Instagram account (@theinvestor_id) by analyzing it through The Circular Model of SoMe, covering the stages of Share, Optimize, Manage, and Engage. Based on the analysis of interview results and documentation from the Instagram account, The Investor, has implemented digital content management according to The Circular Model of SoMe developed by Regina Luttrell. Going forward, research on digital content remains important, considering the rapid and unpredictable development of information and communication technology. The results of research on digital content will be very beneficial for both business practitioners and the advancement of knowledge.